Pengaruh Metode Pembelajaran Problem Solving terhadap Kemampuan Berfikir Kritis dan Motivasi Siswa Materi Perdagangan Internasional di MTSn 1 Kota Blitar - Dewi Sophia Ariani; Hendra Pratama (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to determine whether the problem solving method can improve critical thinking skills and motivation of class VII students at Mtsn 1 Kota Blitar. The researcher used a quantitative research method, using a control class and an experimental class. The study was conducted with 36 students in the control class and 38 students in the experimental class. The results of the T-Test on the critical thinking questionnaire showed that there was a significant difference between the problem solving learning model and students' critical thinking, this is evidenced by a significance value of 0.73. The decision of 0.73> 0.05 indicates that Ho is rejected and Ha is accepted, the results of the T-Test on the learning motivation questionnaire show that there is a significant difference between the problem solving learning model and students' learning motivation, this can be proven by a significance value of 0.001. The decision where 0.001> 0.05 indicates that H0 is rejected while Ha is accepted. The results of the T-Test on student learning outcomes obtained from the pre-test and post-test show that there is a significant influence between the problem solving learning model and student learning outcomes. This is proven by a significance value of 0.000. The decision where 0.000>0.05 indicates that H0 is rejected while Ha is accepted.